Changes in a Company’s Current Dividend Level and Their Impact on Future Profits – Theory and Practice - Zyguła, Andrzej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
According to the signalling theory, investors draw conclusions concerning the future income potential of a given company based on the dividends it pays. According to one of the implications of this theory, changes made to a dividend should mirror the direction of future profits. This article presents an empirical analysis of the relationship between the current changes in the level of a dividend paid (t0) and future company profitability (t + 1, t + 2). The companies examined were all traded on the Warsaw Stock Exchange and paid dividends in the years 2001–2013. The research shows that there is no statistically significant relationship between the dividend paid in a given year and the future results obtained by the companies examined.